A Literature Review on the Impact of Wildfires on Emergency Departments: Enhancing Disaster Preparedness. Issue 5 (25th October 2022) - Skinner, Richard; Luther, Matt; Hertelendy, Attila J.; Khorram-Manesh, Amir; Sørensen, Jarle; Goniewicz, Krzysztof; Ranse, Jamie
Abstract: Introduction: Global climate change (global warming) has been identified as the primary factor responsible for the observed increase in frequency and severity of wildfires (also known as bushfires in some countries) throughout the majority of the world's vegetated environments. This trend is predicted to continue, causing significant adverse health effects to nearby residential populations and placing a potential strain on local emergency departments (EDs). Study Objective: The aim of this literature review was to identify papers relating to wildfires and their impact on EDs, specifically patient presentation characteristics, resource utilization, and patient outcomes. Method: This integrative literature review was guided by the Preferred Reporting Items of Systematic Reviews and Meta-Analysis (PRISMA) guidelines for data collection, and Whittemore and Knafl's framework for data analysis. Data were collected from OvidSP, MEDLINE, DARE, CINAHL, PubMed, and Scopus databases. Various Medical Subject Headings (MeSH) and keywords identified papers relevant to wildfires/bushfires and EDs. Results: Literature regarding the relationship between ED presentations and wildfire events, however, is primarily limited to studies from the United States and Australia and indicates particulate matter (PM) is principally linked to adverse respiratory and cardiovascular outcomes. Observable trends in the literature principally included a significant increase in respiratory presentations, primarily with a lag of one to two days from the initial event. Respiratory and cardiovascular studies that stratified results by age indicated individuals under five, over 65, or those with pre-existing conditions formed the majority of ED presentations. Conclusion: Key learnings from this review included the need for effective and targeted community advisory programs/procedures, prior to and during wildfire events, as well as pre-event planning, development, and robust resilience strategies for EDs.